Analisis Rekonsiliasi Fiskal Pada Laporan Keuangan Komersial Pada PT AIUEO Tahun 2021 - Kayla Tsabita; Yoel Bryan Hamonangan; Saputra, Adrian Daniel (Value : Journal of Management and Business, 2022)
Currently, the world is being hit by the Covid-19 pandemic which has resulted in many companies experiencing a decrease in profit levels, in Indonesia one of which has happened to Pizza Hut Karawang Central Plaza (KCP), so companies have to make new strategies by opening booths on the side of the road and strengthening promotional strategies to increase interest buying consumers. This study aims to examine the effect partially and simultaneously of promotion and location variables on buying interest at Pizza Hut KCP, using quantitative methods and technical data analysis in the form of path analysis. The population in this study was Pizza Hut KCP consumers with a sample of 100 respondents taken using a finite population with the Slovin formula. There is a very strong correlation between promotion and location of 0.800. There is a partial influence of each between promotion and location on purchase intention with values of 47.1% and 32.8% respectively and the simultaneous effect of promotion and location on purchase intention of 57.7%, this shows that respectively it has a positive and significant effect, while the remaining 42.3% is the contribution of other variables not examined in this study.